WNT AGONIST DECREASES TISSUE DAMAGE AND IMPROVES RENAL FUNCTION AFTER ISCHEMIA-REPERFUSION - Kuncewitch, Michael (Shock, 2015)
Renal ischemia-reperfusion (IR) injury (IRI) following shock states or transplantation causes tissue damage and delayed graft function, respectively. The Wnt/β-catenin signaling pathway plays a critical role in nephrogenesis. We therefore hypothesized that pharmacological activation of Wnt/β-catenin signaling by Wnt agonist, a synthetic pyrimidine, could protect kidneys from IRI. Adult male rats were subjected to bilateral clamping of the renal pedicles with microvascular clips for 60 min, followed by reperfusion. Wnt agonist (5 mg/kg BW) or vehicle (20% DMSO in saline) was administered intravenously 1 h prior to ischemia. Blood and renal tissues were collected 24 h after IR for evaluation. Renal IR caused a significant reduction of β-catenin and its downstream target gene cyclin D1 by 65% and 39%, respectively, compared to the sham, while Wnt agonist restored them to the sham levels. The number and intensity of cells staining with the proliferation marker Ki67 in ischematized kidneys were enhanced by Wnt agonist. The integrity of the renal histological architecture in the Wnt agonist group was better preserved than the vehicle group. Wnt agonist significantly lowered serum levels of creatinine, AST, and LDH, inhibited the production of IL-6 and IL-1β, and MPO activities. Lastly, Wnt agonist reduced iNOS, nitrotyrosine proteins and 4-hydroxynonenal in the kidneys by 60%, 47% and 21%, respectively, compared to the vehicle. These results indicate that Wnt agonist improves renal regeneration and function while attenuating inflammation and oxidative stress in the kidneys after IR. Thus, pharmacologic stimulation of Wnt/β-catenin signaling provides a beneficial effect on the prevention of renal IRI.